Implications of Constitutional Legal Policies on Business Practices: Analysis of Economic Rights Protection and Corporate Regulation - Mastur, Mastur; Afif, Muhammad Nur; Bahari, Anggri Septa (LifeSciFi, 2024)
Constitutional law policy has important implications for corporate regulation and the protection of economic rights, yet regulatory challenges often hamper efficiency and innovation. This calls for exploring how constitutional law policies impact business practices and the protection of economic rights. This research uses a quantitative method with a case study approach in the manufacturing sector. The population in this study were managers or policy holders with a sample size of 100 respondents. Primary data was obtained through structured questionnaires distributed to respondents and secondary data was obtained through literature studies. Data analysis was performed using correlation and linear regression analysis. The results showed a significant positive correlation between constitutional policies and business practices and the protection of economic rights. Linear regression analysis showed that constitutional policies and business practices significantly influence the protection of economic rights. The implication of this study is the need to strengthen adaptive constitutional legal policies and sustainable business practices in the manufacturing sector to support inclusive economic growth and protect economic rights with a focus on improving regulations, innovation in business practices, and raising awareness of the importance of regulatory compliance and business sustainability in a dynamic environment.